Low‐SES Children's Eyewitness Memory: The Effects of Verbal Labels and Vocabulary Skills. (13th November 2014) - Chae, Yoojin; Kulkofsky, Sarah; Debaran, Francisco; Wang, Qi; Hart, Sybil L.; Hobbs, Sue D.; Goodman, Gail S.
<x xml:space="preserve">Abstract</x> This study examined the effects of the verbal labels procedure and vocabulary skills on low‐socioeconomic status (SES) preschool children's eyewitness memory. Children (N =176) aged 3–5 years witnessed a conflict event and were then questioned about it in either a standard or a verbal labels interview. Findings revealed that children with higher rather than lower vocabulary skills produced more complete and accurate memories. Children who were given the verbal labels interview recalled more information, which included both correct and incorrect details. Overall, the verbal labels procedure did not improve children's performance on direct questions, but children with low vocabulary skills answered direct questions more accurately if they were given the verbal labels interview than when they were not. Implications of the findings for memory performance of low‐SES children are discussed. Copyright © 2014 John Wiley & Sons, Ltd.